2019
DOI: 10.1037/sgd0000336
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and gender identity victimization among young adults in the New York City metropolitan area: The P18 cohort study.

Abstract: Sexual and gender minority populations are significantly more likely to experience verbal and physical victimization in young adulthood. These analyses examine the types, contexts, and sources of lifetime sexual orientation and gender identity victimization (SGV) in a diverse sample of sexual minority men (SMM) and transgender women as well as the extent to which experiences of SGV vary among subgroups of the population. Cross-sectional data were collected as part of a study of sexual health, mental health, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We reported results according to the Strengthening the Reporting of Observational Studies in Epidemiology guidelines for cross-sectional studies (von Elm et al, 2008). Findings related to cigarette smoking and substance use (LoSchiavo et al, 2019), sexualized and gendered-based violence (LoSchiavo et al, 2021), and HIV risk (Halkitis et al, 2015) using data from the P18 Cohort Study are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported results according to the Strengthening the Reporting of Observational Studies in Epidemiology guidelines for cross-sectional studies (von Elm et al, 2008). Findings related to cigarette smoking and substance use (LoSchiavo et al, 2019), sexualized and gendered-based violence (LoSchiavo et al, 2021), and HIV risk (Halkitis et al, 2015) using data from the P18 Cohort Study are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual orientation was measured using a single item based on the Kinsey scale (Kinsey et al, 1948), with values ranging from exclusively heterosexual (1) to exclusively homosexual (7). Similar to previous studies, we dichotomized sexual orientation as exclusively homosexual or not exclusively homosexual (LoSchiavo et al, 2019). Response options for gender identity included male, female, transfemale, genderqueer, or no gender; we dichotomized responses as cisgender male or transgender due to the small number of noncisgender male participants.…”
Section: Demographicsmentioning
confidence: 99%
“…Despite this evidence, researchers have not considered the ACEs and CVD association among people with HIV (PWH). This is a key omission in the literature because PWH and those at risk for acquiring HIV, including sexual and gender minority populations, tend to experience more ACEs than people without HIV [3,[13][14][15][16]. Moreover, people with ACEs are more likely to experience intimate partner violence and other abuses later in life [17], particularly women living with HIV (WLWH) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…From this, it would be possible to promote the monitoring of the needs of this population, respecting and guaranteeing human rights and providing quality information about medical care, reducing stigmatization. (3,(16)(17)(18)(19) Thus, the present study aimed to raise, based on published scientific evidence, the relevant aspects about the mental health of transgender children and adolescents, in addition to seeking the impacts of strategies, such as social transition and family support, in reducing psychopathological problems and improving the quality of life of this population.…”
Section: Introductionmentioning
confidence: 99%